Chlorhexidine increases the longevity of in vivo resin-dentin bonds - Ricci, Herica A. [UNESP]; Sanabe, Mariane E. [UNESP]; de Souza Costa, Carlos A. [UNESP]; Pashley, David H.; Hebling, Josimeri [UNESP] (Wiley-Blackwell, 2010)
The aim of this study was to evaluate the mechanical stability of resin-dentin bonds produced in vivo in the presence of chlorhexidine. Children presenting at least one pair of contralateral primary molars with occlusal carious lesions were enrolled in the study. After cavity preparation and phosphoric acid etching, dentin was treated with 5 mu l of either 2% chlorhexidine (control group) or deionized water (experimental group). Thirteen pairs of teeth were restored and were collected after physiological exfoliation. The periods in oral function after restoration were divided as follows: up to 30 d; and 1-5, 10-12, and 18-20 months. Beam-shaped specimens (0.81 mm2) were obtained and subjected to microtensile bond-strength testing. A significant decrease of the bond strength was observed in the control group starting at the 1-5 month period (30.6%), while in the experimental group this decrease started only after 10-12 months of function (26.3%). The use of chlorhexidine as an adjuvant to the adhesion to dentin did not produce any detrimental effect to the immediate bond strength and was capable of reducing the rate of resin-dentin bond degradation within the first few months after restoration.
Keywords: chlorhexidine; dentin; dentin-bonding agents; longevity; tensile strength